2005
DOI: 10.1055/s-2005-864102
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Diterpenoids from the Roots ofEuphorbia ebracteolata

Abstract: Three new diterpenoids, yuexiandajisu D (1), E (2) and F were isolated from the roots of Euphorbia ebracteolata, along with eight known diterpenoids, jolkinolide B (4), jolkinolide A, ent-11alpha-hydroxyabieta-8(14),13(15)-dien-16,12alpha-olide (6), ent-(13S)-hydroxyatis-16-ene-3,14-dione, ent-3beta,(13S)-dihydroxyatis-16-en-14-one, ent-3-oxokaurane-16alpha,17-diol, ent-16alpha,17-dihydroxyatisan-3-one and ent-atisane-3beta,16alpha,17-triol. The structures of all compounds were deduced using spectroscopic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 5 publications
0
59
0
Order By: Relevance
“…The Euphorbia is known to contain skin irritants and co-carcinogenic principles in the form of esters of the structurally related diterpenes ingenane and daphanane (Hecker, 1978;Evans and Taylor, 1983;Hecker et al, 1984). Earlier studies undertaken on this genus have revealed the presence of triterpenes (Lima et al, 2003), diterpenes (Shi et al, 2005), macrocyclic diterpenes (Redei, et al, 2003) and aromatic compounds (Oksuz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Euphorbia is known to contain skin irritants and co-carcinogenic principles in the form of esters of the structurally related diterpenes ingenane and daphanane (Hecker, 1978;Evans and Taylor, 1983;Hecker et al, 1984). Earlier studies undertaken on this genus have revealed the presence of triterpenes (Lima et al, 2003), diterpenes (Shi et al, 2005), macrocyclic diterpenes (Redei, et al, 2003) and aromatic compounds (Oksuz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The dried plant roots of Euphorbia fischeriana Steud (Euphorbiaceae), known as ''lang-du'' in traditional Chinese medicine, have long been used for the treatment of cancer, edema, and ascites (36)(37)(38)(39). Diterpenoids are major chemical constituents of the roots constituting f0.1% of the plant's total mass.…”
Section: Introductionmentioning
confidence: 99%
“…Many study reports [3][4][5][6] have confirmed that E. ebracteolata can be used to treat cancer. In the present study, we studied the effects of EA and EB from E. ebracteolata on the proliferation of HepG2 cells and the possible mechanisms in vitro by MTT, flow cytometry and Western blot assays.…”
Section: Discussionmentioning
confidence: 99%
“…Yuexiandajisu D from E. ebracteolata inhibits the proliferation of HCT-8, KB, A549, Bel-7402 and BGC-823 cells [5]. Jolkinolide B and ent-11α-hydroxyabieta-8 (14),13(15)-dien-16,12α-olide from E. ebracteolata show cytotoxicity activities against ANA-1, B16 and Jurkat cells [6]. In addition, the terpenoids from Euphorbia L. show cytotoxic activities against SMMC-7221, L342, MCc80-3, U937 and HeLa cells, and their anti-cancer mechanisms may be related to apoptosis [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation